Optimizing vermicompost-soil ratios for synergistic enhancement of Allium fistulosum growth dynamics and phytochemical quality - Gong, Shuangmei; Ou, Xiulong (Frontiers in Plant Science, 2025)
To determine the optimal vermicompost application ratio in vegetable cultivation, this study focused on Allium fistulosum (variety NC89) and conducted a pot experiment with five treatments, using vermicompost-to-soil mass ratios of 0% (control), 25%, 50%, 75%, and 100%. Growth indicators and quality parameters were measured, and the vermicompost effect was analyzed based on morphological characteristics. Results showed that under the 50% treatment, the vitamin C and soluble sugar contents of A. fistulosum were significantly higher than those under other treatments. The biological yield and fresh weight were relatively high, and growth indicators such as root length and plant height were well - coordinated. The number of tillers was significantly greater, with dark green leaves and compact texture. The 75% treatment had the lowest nitrate content, but its growth indicators were slightly inferior to those under the 50% treatment. A comprehensive analysis indicated that a 50% vermicompost-to-soil ratio could synergistically improve A. fistulosum yield and quality by enhancing soil aeration and balancing nutrient supply. This study provides a theoretical basis and technical reference for rational vermicompost application in protected vegetable cultivation.